2017
DOI: 10.1590/1679-78253162
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Welding of AZ31 Magnesium Alloys - A Numerical and Experimental Study

Abstract: In this paper, weldability of magnesium alloys by friction stir welding (FSW) method which is difficult to join by the fusion welding have been investigated experimentally and numerically. To this end, the connection of magnesium alloys was performed using different welding parameters. AZ31 Mg-alloy plates were friction stir welded at rotation speed of 1200 rev/min and translational speeds of 80,100,120,140 mm/min. Temperature evolution in the weld zone during welding was measured by using embedded K-type ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
10
2
Order By: Relevance
“…By the way, it should be noted once again that the friction and plastic deformation play a significant role on the generated heat during the process. Besides, it is widely accepted that the microstructure and mechanical features of joint are considerably influenced by the generated heat (Serindag and Kiral 2017). It has been reported that the tool rotational speed has more influence on the frictional energy by comparison with other major FSW parameters such as the axial plunge force and welding speed (Aziz et al 2016).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…By the way, it should be noted once again that the friction and plastic deformation play a significant role on the generated heat during the process. Besides, it is widely accepted that the microstructure and mechanical features of joint are considerably influenced by the generated heat (Serindag and Kiral 2017). It has been reported that the tool rotational speed has more influence on the frictional energy by comparison with other major FSW parameters such as the axial plunge force and welding speed (Aziz et al 2016).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…While the peak values measured at R 1 , R 3 and R 5 are 289 • C, 333 • C, 375 • C. Such a temperature field is commonly found during the FSW process [23,[38][39][40][41]. The distinctions of the peak temperature along the welding direction (WD) are even still presented when the heat pipe is applied in the FSW process, as well as the differences of the temperatures along the transverse direction (the direction perpendicular to the welding direction on the welded plates, which is often abbreviated as TD) [42]. The larger heat loss and unstable generated heat at the beginning of the welding restrict the temperature rising (such as A 1 and R 1 ) [43].…”
Section: Measurement Of Hardnessmentioning
confidence: 99%
“…Using the design principle shown in Figure 1, which is commonly used for the simplest sizing, spot-welding design can be generated as given by equation 1[1] based on the mean shear stress ( ) [3]. A few earlier research reported on the stress mechanisms at the overlapped joints [2][3][4][5][6][7][8][9][10][11][12]. Shen Z. have been investigated AA7075-T6 Aluminum sheet with a mean yield value of 500 MPa and the intended result was achieved only for elastic-elastic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Transient nonlinear finite element analyses were performed to make structural stress analysis. It has seen that the welding performance increases as both low transverse speed and high rotational speed increase [7]. In that study, nonlinear ultimate stress analysis has been performed with nonlinear material information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation